Bridging the Gap Between Environmental Adversity and Neuropsychiatric Disorders: The Role of Transposable Elements - DeRosa, Holly; Richter, Troy; Wilkinson, Cooper; Hunter, Richard G. (Frontiers in Genetics, 2022)
Long regarded as “junk DNA,” transposable elements (TEs) have recently garnered much attention for their role in promoting genetic diversity and plasticity. While many processes involved in mammalian development require TE activity, deleterious TE insertions are a hallmark of several psychiatric disorders. Moreover, stressful events including exposure to gestational infection and trauma, are major risk factors for developing psychiatric illnesses. Here, we will provide evidence demonstrating the intersection of stressful events, atypical TE expression, and their epigenetic regulation, which may explain how neuropsychiatric phenotypes manifest. In this way, TEs may be the “bridge” between environmental perturbations and psychopathology.